2019
DOI: 10.21203/rs.2.18796/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NLRC3 delays the progression of AD in APP/PS1 mice via inhibiting PI3K activation

Abstract: Background/Aims: NLRC3 inhibits inflammatory responses. Epidemiological studies indicate that neuroinflammation induces and accelerates the onset of Alzheimer's disease (AD). This study was designed to determine whether NLRC3 plays a role in neuroinflammation, Aβ accumulation and neuroprotection in AD mice.Methods: Thirty 12-month-old APP/PS1 transgenic mice were randomized into three groups as model group, APP/PS1 +LVCON307 and APP/PS1 +LV-NLRC3 group. Ten 12-month-old wild-type C57 mice were chosen as contro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…[41] Specifically, a recent preprint reported that downregulation of NLRC3 in a mouse model affects plaque deposition and neuronal loss. [42] Thus, we speculate that rare variants in NLRC3 elevate inflammation, resulting in increased neurodegeneration and dementia symptoms. GABBR2 and CASZ1 were genes identified with Non-AD synaptic functioning in protein-coding models, as mainly represented by higher levels of neurogranin.…”
Section: Discussionmentioning
confidence: 90%
“…[41] Specifically, a recent preprint reported that downregulation of NLRC3 in a mouse model affects plaque deposition and neuronal loss. [42] Thus, we speculate that rare variants in NLRC3 elevate inflammation, resulting in increased neurodegeneration and dementia symptoms. GABBR2 and CASZ1 were genes identified with Non-AD synaptic functioning in protein-coding models, as mainly represented by higher levels of neurogranin.…”
Section: Discussionmentioning
confidence: 90%